PENERAPAN PERMAINAN BALOK DALAM MENGEMBANGKAN KECERDASAN VISUAL SPASIAL ANAK USIA DINI - Ika Yatri; Nur Amini (Institut Madani Nusantara, 2022)
Block games are tools in teaching and learning activities by using pieces that resemble wood which are the same thickness and with a length of twice or four times the same size, some are in the form of curves, cylinders and half of the pieces of blocks are also provided, but all of the same length. according to the size of the base beams. Visual-spatial intelligence is an ability related to combining the characteristics of objects or objects in the surrounding environment in the form of mental images that can be re-expressed in the form of detailed information, pictures, paintings, sculptures, and others. This intelligence involves sensitivity to color, line, shape, size, area, and the relationship between these elements. The purpose of this study was to determine how the application of block games can develop visual-spatial intelligence in early childhood at RA Al Kautsar Cibatu Cisaat. This research uses a qualitative descriptive research type. Data collection techniques that researchers use in this study are observation, interview, and documentation techniques. While the data analysis techniques used are data reduction, data display and drawing conclusions. Based on this analysis, the researchers presented the results of the study that the development of visual spatial intelligence of children aged 5-6 years at RA Al Kautsar Cibatu Cisaat generally has good value because of the 4 indicators put forward by researchers not all of them have developed as expected. Based on the results of the analysis and discussion that the researchers have described, not all children are enthusiastic in participating in the block game and there are also some children who have not made construction using the block game.